2021
DOI: 10.1021/acs.langmuir.0c03316
|View full text |Cite
|
Sign up to set email alerts
|

Structural Tunability on Naphthalimide-Based Dendrimer Gelators via Glaser Coupling Interaction with Tailored Gelation Solvent Polarity and Stimuli-Responsive Properties

Abstract: To date, most of the low-molecular-weight gels are found serendipitously, and modification on known gelator structures via organic synthesis is an efficient methodology to prepare gel series. However, a simple, direct, and rational modification method for a known gelator is still a challenge. Herein, we employ Glaser coupling reaction to synthesize a novel dendrimer gelator BisDEC with the (ALS2)2 structure, starting from terminal alkyne-based gelator DEC with the ALS2 structure. This structural change results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The modification of these functional groups will lead to the alteration of specific interactions arising from the particular functional group, which can be considered as an excellent strategy to evaluate the role of specific interactions in gel formation [30,31]. For example, Zinchuan et al have synthesized a cholesterol-based dendrimer gelator from the parent terminal alkyne-based gelator and have shown that the modified compounds formed gel in polar solvents compared to the parent compound, which only formed gel in nonpolar solvents [32]. McNeil's group has developed nitrite sensor-based LMWGs from a known azosulfonate gelator scaffold [33].…”
Section: Introductionmentioning
confidence: 99%
“…The modification of these functional groups will lead to the alteration of specific interactions arising from the particular functional group, which can be considered as an excellent strategy to evaluate the role of specific interactions in gel formation [30,31]. For example, Zinchuan et al have synthesized a cholesterol-based dendrimer gelator from the parent terminal alkyne-based gelator and have shown that the modified compounds formed gel in polar solvents compared to the parent compound, which only formed gel in nonpolar solvents [32]. McNeil's group has developed nitrite sensor-based LMWGs from a known azosulfonate gelator scaffold [33].…”
Section: Introductionmentioning
confidence: 99%